Influence of the Geometric Parameter on the Regimes of Natural Convection and Thermal Surface Radiation in a Closed Parallelepiped; Journal of Engineering Physics and Thermophysics; Vol. 88, iss. 6 - Martyushev S. G. (2015, 2015)
Title screen